Development and Validation of Multiple-Choice Assessment Tool in Undergraduate Genetics Using Rasch Modeling - Mahawan, Alvin M.; Banzuelo, Je-Ann R.; Peria, Jo Neil T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
ABSTRACT In response to persistent gaps in genetics literacy and the lack of validated assessment tools, this study developed and validated a 40-item multiple-choice assessment tool in undergraduate Genetics using Rasch modeling. The need for this tool arises from curriculum mandates, such as the Commission on Higher Education’s (CHED) Outcomes-Based Education (OBE) framework, and global calls for equitable, high-quality science education aligned with SDG 4 and the OECD’s science competency benchmarks. Using a developmental research design, the tool was constructed based on key Genetics concepts aligned with the Philippine BSED Science curriculum. Items were reviewed by Genetics experts for content validity. The instrument was pilot-tested among 200 undergraduates using stratified random sampling to ensure representation across gender and academic backgrounds. Rasch analysis was conducted using R Studio (TAM and eRm packages) to evaluate item fit, unidimensionality, difficulty targeting, differential item functioning (DIF), and reliability. Results indicated that 33 of 40 items demonstrated good model fit, with a principal component analysis (PCA) eigenvalue of 1.9 supporting unidimensionality. The item-person map showed that item difficulty aligned well with student ability levels, with minimal ceiling and floor effects. DIF analysis confirmed measurement invariance across gender and academic background, with all DIF contrast values falling within ±0.5 logits. Reliability indices were high (KR-20 and Cronbach’s Alpha = 0.87), and person separation index was 2.6, confirming the tool’s capacity to differentiate among multiple ability levels. The study concludes that the developed tool is psychometrically sound, equitable, and instructionally valuable. It is recommended for use in undergraduate Genetics courses for diagnostic and summative assessment. Future research may expand the tool to broader domains in Genetics and evaluate its impact on instructional quality and student learning outcomes.